KARAKTERISTIK FISIKOKIMIA MIKROENKAPSULAN ANTOSIANIN DARI LIMBAH CAIR PENGOLAHAN PATI UBI JALAR UNGU (Physicochemical Characteristics of Anthocyanin Microencapsulant from Wastewater of Purple Sweet Potato Starch Processing) - Dessy Wiriani; Elisa Julianti; Hotnida Sinaga (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2020)
Wastewater from starch processing of purple sweet potato (PSP) was rich in anthocyanin, so it can be used as raw material for natural pigments. Anthocyanin pigments are unstable under processing conditions so microencapsulation is carried out to maintain their stability. This study aims to evaluate the effect of maltodextrin concentration as an encapsulant agent on the physical and chemical characteristics of microencapsulant of anthocyanin derived from wastewater of PSP starch processing. Wastewater from PSP starch processing was concentrated using a water bath at 10 oC for 10 hours. The crude extract of anthocyanin obtained then was microencapsulated by spray drying technique using maltodextrin as an encapsulant agent. Maltodextrin was added at concentration 15%, 25%, and 35% (w/w). The anthocyanin microencapsulants produced then were evaluated for their physical and chemical characteristics. The results showed the increasing of maltodextrin concentration will increase the L* value (lightness), b* value (greenness), ohue, solubility, hygroscopicity, but decrease the anthocyanin content, a* value (redness) and and antioxidant activity (IC50). The microstructure of anthocyanin microencapsulant has a spherical shape with a curve on its surface. The addition of 15% maltodextrin produces the best characteristics of anthocyanin microencapsulant with anthocyanin content 40.80 ppm, IC50 36.27 ppm, solubility 52.80% and color value (oHue) 11.17 (red purple). These characteristics indicate that anthocyanin microencapsulant from wastewater of PSP starch processing can be applicated as natural food colorant.Keywords: anthocyanin microencapsulant, purple sweet potato, wastewater, maltodextrin